La experimentación como estrategia para el aprendizaje de formación de compuestos y reacciones químicas con los estudiantes de primero de Bachillerato General Unificado del Colegio de Bachillerato Chambo. - Quintanilla Guerrero, Verónica Rocío (2024)
The present research was developed at the Chambo High School, the participating students were from the first year of the Unified General High School parallel A and B, and the objective of the study is to apply experimentation for learning the formation of compounds and Chemical reactions. The research is correlational and used since it was proposed to evaluate the incidence of experimentation on the student's academic performance. The research population was selected intentionally, and two groups were formed, namely, the control group and the experimental group, each consisting of twenty-one students. The data collection was carried out by applying pretest and posttest to the control and experimental groups, the SPSS statistical software was used in the data processing, which allowed the comparison of averages and the determination of the p-value through the t-test for independent samples to verify the hypothesis, a satisfaction survey was also applied. The results show that experimentation positively impacts learning the formation of compounds and Chemical reactions and that students have a high degree of interest in participating in classes with experimental activities.